FAKTOR-FAKTOR YANG MEMPENGARUHI BANJIR PADA SALURAN DRAINASE SISTEM III DI KOTA SINGARAJA - N Surayasa; I N Merit; I N Sunarta (Master Program of Environmental Science, Postgraduate Program of Udayana University)
The problems which arise in every rainy season in Singaraja are flood and the back up of water. They are caused by the inability of totally functioning drainage system. The lack of awareness and participation of the society in maintaining the drainage system nearby causes clogging in the drainage system caused by industrial garbage or those come from houses. This research is aimed at knowing the suibility of the debit capacity of drainage system and the factors causing flood in drainage system III in Singaraja city. The reason why the analysis of flood was conducted is because flood often appears in this location, and in this city there are also : (1) area of water source called Mumbul (source of fresh water or municipal waterworks). If the flood flows into this area, it will be worrying that the water will be polluted and the water pump will be broken, (2) market, (3) shopping area, and (4) housing. This research was conducted since March until June 2008 at drainage system III in Singaraja city around Tasbih street, Anggrek street, Leli street, Kenanga street, Flamboyan street, Tukad Mumbul, and A.Yani street. To know the debit capacity of the drainage system (Qs) and factors causing flood in drainage system III in Singaraja city, the analysis using mathematical model was conducted, in this case drainage dimension, debit surface running of water (Qp), and flood debit (Qb) were used as the input. Meanwhile, the factors influencing why the society threw garbage into the drainage were analyzed based on the descriptive method. The result of the research shows that the capacity the debit at Tasbih street, Leli street, Anggrek street, A. Yani Street, Flamboyan street, as well as Tukad Mumbul have been over the capacity, while the capacity of drainage debit at Anggrek and Kenanga Street have matched with planned condition (environment condition), with the Qs=74,66 m3/second; Qp=115,68 m3/second; Qb=6,79 m3/second. From the mathematical model analysis we got contribution of debit caused by change of environment (Ql)=45,27 m3/second and the debit caused by social behavior (Qm)=6,35 m3/second. The act of society that brings effect to flood is the act of throwing garbage in disposal area and this causes the increase of water debit until 3,37 m3/second; keeping the garbage in an empty place causes the increase of 0,56 m3/second; and directly throwing garbage into the drainage (upper course) causes the increase of 2,25 m3/second. Factors affecting society throwing garbage into drainage are : lack of disposal area, no punishment for those who break the rule (28,57%), the society’s view on dirty place of drainage system (71,43%) and the permissive society to the rule of throwing garbage (71,43%).